Alpha-mangostin from mangosteen (Garcinia mangostana Linn.) pericarp extract reduces high fat-diet induced hepatic steatosis in rats by regulating mitochondria function and apoptosis. Issue 1 (December 2016) - Tsai, Shin-Yu; Chung, Pei-Chin; Owaga, Eddy; Tsai, I-Jong; Wang, Pei-Yuan; Tsai, Jeng-I; Yeh, Tien-Shun; Hsieh, Rong-Hong
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is caused by multiple factors including hepatic oxidative stress, lipotoxicity, and mitochondrial dysfunction. Obesity is among the risk factors for NAFLD alongside type 2 diabetes mellitus and hyperlipidemia. α- mangostin (α-MG) extracts from the pericarps of mangosteen (Garcinia mangostana Linn.) may regulate high fat diet-induced hepatic steatosis; however the underlying mechanisms remain unknown. The aim of this study was to investigate the regulatory effect of α-MG on high fat diet-induced hepatic steatosis and the underlying mechanisms related to mitochondrial functionality and apoptosis in vivo and in vitro. Methods Sprague Dawley (SD) rats were fed on either AIM 93-M control diet, a high-fat diet (HFD), or high-fat diet supplemented with 25 mg/day mangosteen pericarp extract (MGE) for 11 weeks. Thereafter, the following were determined: body weight change, plasma free fatty acids, liver triglyceride content, antioxidant enzymes (superoxide dismutase, SOD; glutathione, GSH; glutathione peroxidase, GPx; glutathione reductase GRd; catalase, CAT) and mitochondrial complex enzyme activities. In the in vitro study, primary liver cells were treated with 1 mM free fatty acid (FFA) (palmitate: oleate acid = 2:0.25) to induce steatosis. Thereafter, the effects of α-MG (10 μM, 20 μM, 30 μM) on total and mitochondria ROS (tROS, mitoROS), mitochondria bioenergetic functions, and mitochondrial pathway of apoptosis were examined in the FFA-treated primary liver cells. Results The MGE group showed significantly decreased plasma free fatty acids and hepatic triglycerides (TG) and thiorbarbituric acid reactive substances (TBARS) levels; increased activities of antioxidant enzymes (SOD, GSH, GPx, GRd, CAT); and enhanced NADH-cytochromec reductase (NCCR) and succinate-cytochromec reductase (SCCR) activities in the liver tissue compared with HFD group. In the in vitro study, α-MG significantly increased mitochondrial membrane potential, enhanced cellular oxygen consumption rate (OCR), decreased tROS (total ROS) and mitoROS (mitochondrial ROS) levels ; reduced Ca2+ and cytochromec (cytc ) release from mitochondria, and reduced caspases 9 and 3 activities compared with control group. Conclusion These findings demonstrate α-MG attenuated hepatic steatosis in high fat-diet fed rats potentially through enhanced cellular antioxidant capacity and improved mitochondrial functions as well as suppressed apoptosis of hepatocytes. The findings of study represent a novel nutritional approach on the use of α-MG in the prevention and management of NAFLD.